Water resources of Latin America and the Caribbean and their utilization : a report on progress in the application of the Mar del Plata Action Plan (United Nations SantiagoCL, 1985)
Focuses on the assessment of water resources; water use and efficiency; environment, health and pollution control; institutional and legal structure for water resource planning and management; natural hazards; education and training; and regional and international co-operation.
DC